Synthesis and characterization of zeolites from coal fly ash for purification of alpha amylases - Nitin, Goyal (My University, 2013)
The biotechnological potential of α-amylases from microorganisms has drawn a great deal of attention from various researchers worldwide as likely biological catalysts in a variety of industrial processes. Currently recovery of alpha amylase from the various culture broths represent a complex engineering problem, involving multi-step schemes that lead to significant loss of the desired bio product by conventional methods. The bio product is not only present in very low concentrations, but also it is subject to chemical/enzymatic degradation. An alternative cost-effective method for bio separation/recovery of proteins in a highly purified form may be through adsorption, which is a separation technique based on specific and reversible binding via biological reactions. In the present study, a cheap source i.e coal fly ash was used to synthesize three types of zeolites by alkali fusion followed by hydrothermal treatment. The synthesized zeolites were characterized through XRD (X-Ray Diffraction), SEM (Scanning Electron Microscope) and FTIR (Fourier Transform Infrared Spectroscopy) techniques. The cost of production of synthesized zeolites was estimated to be almost one-fifth of that of commercial zeolites available in the market. The effective adsorption of alpha amylases from bacterial culture by newly synthesized adsorbents was studied and the recovery of alpha amylase from zeolites was performed by desorption. The recovery of α-amylase was observed to be maximum (73%) in case of zeolite NaX. The results of the present study are encouraging for the use of zeolites for purification of industrially important alpha-amylases economically.
Master of Science-Biotechnology, Dissertation
Keywords: Adsorption; alpha amylase; coal fly ash; zeolites